Analysis of Production Scale and Input Elasticity of Clove Farming in Umejero Village, Busungbiu District, Buleleng Regency - Ni Putu Eka Aprilia Dewi; Ni Nyoman Reni Suasih (International Journal of Economics, Management and Accounting, 2025)
Plantation agriculture encompasses all activities involving the cultivation of specific crops and the commercialization of their products and services, supported by science, technology, capital, and management, with the aim of improving the welfare of plantation business actors and the wider community. This study aims to analyze the production scale, input elasticity, and factors affecting clove production in Umejero Village, Busungbiu District, Buleleng Regency. Given the high dependence of farmers on harvest outcomes and price fluctuations, this analysis is essential to understand the impact of economic and agronomic variables such as working capital, labor, land area, and selling price on production output. The study employs a quantitative method using multiple linear regression based on the Cobb-Douglas production function. Data were collected through questionnaires and interviews with clove farmers in Umejero Village using purposive sampling. The results indicate that all four variables simultaneously have a significant effect on clove production, with each variable also having a partial positive influence. The analysis of production scale shows increasing returns to scale, meaning that a proportional increase in all input factors leads to a more than proportional increase in output. The elasticity analysis indicates that capital input is elastic, suggesting that a small increase in capital leads to a disproportionately large increase in output. In contrast, labor, land area, and selling price are inelastic, implying that increases in these inputs result in only modest increases in output. These findings highlight the need for solid policy foundations and strategic initiatives to enhance clove productivity both at the farmer and local government levels. Furthermore, the study’s results are expected to assist farmers in making more informed and sustainable decisions in farm management, ultimately contributing to the improved welfare of clove-farming communities in the region.